Cationic antimicrobial peptides promote microbial mutagenesis and pathoadaptation in chronic infections. - Dominique H Limoli; Andrea B Rockel; Kurtis M Host; Anuvrat Jha; Benjamin T Kopp; Thomas Hollis; Daniel J Wozniak (PLoS Pathogens)
Acquisition of adaptive mutations is essential for microbial persistence during chronic infections. This is particularly evident during chronic Pseudomonas aeruginosa lung infections in cystic fibrosis (CF) patients. Thus far, mutagenesis has been attributed to the generation of reactive species by polymorphonucleocytes (PMN) and antibiotic treatment. However, our current studies of mutagenesis leading to P. aeruginosa mucoid conversion have revealed a potential new mutagen. Our findings confirmed the current view that reactive oxygen species can promote mucoidy in vitro, but revealed PMNs are proficient at inducing mucoid conversion in the absence of an oxidative burst. This led to the discovery that cationic antimicrobial peptides can be mutagenic and promote mucoidy. Of specific interest was the human cathelicidin LL-37, canonically known to disrupt bacterial membranes leading to cell death. An alternative role was revealed at sub-inhibitory concentrations, where LL-37 was found to induce mutations within the mucA gene encoding a negative regulator of mucoidy and to promote rifampin resistance in both P. aeruginosa and Escherichia coli. The mechanism of mutagenesis was found to be dependent upon sub-inhibitory concentrations of LL-37 entering the bacterial cytosol and binding to DNA. LL-37/DNA interactions then promote translesion DNA synthesis by the polymerase DinB, whose error-prone replication potentiates the mutations. A model of LL-37 bound to DNA was generated, which reveals amino termini α-helices of dimerized LL-37 bind the major groove of DNA, with numerous DNA contacts made by LL-37 basic residues. This demonstrates a mutagenic role for antimicrobials previously thought to be insusceptible to resistance by mutation, highlighting a need to further investigate their role in evolution and pathoadaptation in chronic infections.